Approaches Involved in the Vegetable Crops Salt Stress Tolerance Improvement: Present Status and Way Ahead - Behera, Tusar Kanti; Krishna, Ram; Ansari, Waquar Akhter; Aamir, Mohd; Kumar, Pradeep; Kashyap, Sarvesh Pratap; Pandey, Sudhakar; Kole, Chittaranjan (Frontiers in Plant Science, 2022)
Salt stress is one of the most important stresses among abiotic stresses as it persists throughout the plant life cycle. The productivity of crops prominently affected by soil salinization due to bad agricultural practices, increasing human activities, and natural processes. Yearly approximately 12 billion US$ lost worldwide, because of reduction in agriculture production from the salt stressed area. Approximately 10% of the total land area (950 Mha) and 50% of the total irrigated area (230 Mha) in the world are under salt stress. The severity of salt stress will increase in the upcoming next years as the increasing world population and use of poor quality irrigation water. Unfortunately, majority of vegetable crops have very low salinity threshold (EC t ) which ranged (1 to 2.5 dS m -1 in saturated soil) for bean, carrot, celery, eggplant, lettuce, muskmelon, okra, pea, pepper, potato, spinach and tomato. These crops used almost every part of the world and lake novel salt tolerance gene within its gene pool. Salt stress severely affects these crops yield and quality. To resolve this issue, novel genes governing salt tolerance under extreme salt stress identified and transferred to the vegetable crops. The vegetable improvement for salt tolerance will require not only the yield influencing trait but also target those character or trait that directly influencing the environmental stress to the crop developmental stage. Genetic engineering is a potential tool which can improve salt tolerance in vegetable crop regardless of species barriers. In present review details of the various physio-biochemical and molecular aspects involved in salt stress has been explored.